DESIGN OF EDUCATIONAL MEDIA ON DANGER SIGNS OF LABOR TO PREVENT COMPLICATIONS IN EXPECTANT MOTHERS AT BANTAR PUBLIC HEALTH CENTER, TASIKMALAYA CITY - Nurvita, Nita; Gustini, Sri; Wulandara, Qanita (Poltekkes Kemenkes Tasikmalaya, 2025)
This study aimed to develop and validate an audio-visual educational media product titled “MEDITASI” (Media Informasi Tanda Bahaya Persalinan), designed to increase awareness of childbirth danger signs. Using a Research and Development (R&D) approach based on Sugiyono’s model, the research adapted nine steps to create this product. The video was developed with engaging visuals, animations, music, and narration to ensure clarity and appeal. Validation and feasibility testing involved healthcare providers, pregnant women, and community members, resulting in the media being deemed valid and highly appropriate for educational purposes. Small-scale and large-scale trials showed excellent ratings, particularly in visual clarity (92%-94%) and audio appeal (94%-95%). This highlights the effectiveness of audio-visual media in improving comprehension and information retention. The study supports the use of “MEDITASI” as a recommended tool for health education, particularly in maternal health.